Pemanfaatan “Coding Danker” Terhadap Peningkatan Produksi ASI Ibu Menyusui - Nova Yulita; Sarah Fitria; Jumiati Jumiati; Nevy Susianty; Siti Nurkhasanah; M. Azhari Herli Saptadi Putra; Ayu Rahmawati; Maswarni Maswarni; Reni Ardila; Rahmi Nawiti; Ayuni Septiani; Nazla Anugerah Hendri (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
The practice of breastfeeding is one way to optimize the health and development of children. Exclusive breastfeeding for infants 0-6 months without providing complementary foods/substitutes for breast milk. Exclusive breastfeeding problems can be caused by breast milk that does not come out after childbirth, lack of milk production, the inability of the baby to suck, abnormal conditions of the mother's nipples, working mothers, and lack of health information. Health problems that often occur in breastfeeding mothers are reduced milk production, which will later affect breastfeeding status so that it can be a risk factor for stunting. One way to increase the volume of breast milk is to provide Moringa leaf extract as an ingredient to be processed into alternative food products, namely "Coding Danker". This community service activity was carried out three times, namely exclusive breastfeeding and stunting counseling, processing alternative food products from Moringa leaves, providing food products to the community, breastfeeding mothers and monitoring evaluations and interventions from providing Coding Danker to breastfeeding mothers. This activity is aimed at increasing the knowledge and skills of PKK mothers in RW 7 Sialang Munggu Village in making pastries based on local wisdom, namely cookies with Moringa leaf extract. Community service participants were given material by showing videos on how to make these products. The outputs of this community service are one scientific article, one article in print/electronic mass media, activity videos and community service reports.